2021
DOI: 10.3390/brainsci11040459
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Acoustic Sex Differences in Rat Ultrasonic Vocalization

Abstract: The rat model is a useful tool for understanding peripheral and central mechanisms of laryngeal biology. Rats produce ultrasonic vocalizations (USVs) that have communicative intent and are altered by experimental conditions such as social environment, stress, diet, drugs, age, and neurological diseases, validating the rat model’s utility for studying communication and related deficits. Sex differences are apparent in both the rat larynx and USV acoustics and are differentially affected by experimental conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 174 publications
(244 reference statements)
6
20
0
Order By: Relevance
“…This preference of the sham-control rats for stranger over familiar 50-kHz USV cannot be explained by differences between groups in USV files parameters (subtypes composition, total duration and number of calls, mean peak frequency and bandwidth), since they are similar between rats subjected to stranger and familiar USV. However, in accordance with literature (Lenell et al, 2021;Wright et al, 2010), we observed an inter-subject variability in these USV files parameters within groups. Then, this differential preference for familiar vs stranger USV indicates that rats are able to recognize the vocal signature of their cage-mate.…”
Section: Effect Of the Familiarity On The Rewarding Properties Of Usv And Consequences On Cocaine Intakesupporting
confidence: 92%
See 3 more Smart Citations
“…This preference of the sham-control rats for stranger over familiar 50-kHz USV cannot be explained by differences between groups in USV files parameters (subtypes composition, total duration and number of calls, mean peak frequency and bandwidth), since they are similar between rats subjected to stranger and familiar USV. However, in accordance with literature (Lenell et al, 2021;Wright et al, 2010), we observed an inter-subject variability in these USV files parameters within groups. Then, this differential preference for familiar vs stranger USV indicates that rats are able to recognize the vocal signature of their cage-mate.…”
Section: Effect Of the Familiarity On The Rewarding Properties Of Usv And Consequences On Cocaine Intakesupporting
confidence: 92%
“…It is important to note that this study was exclusively conducted on male rats, as a first step before testing female rats, although they do not seem to show social novelty preference (Veenema et al, 2012) and emit less USV than males (for review see Lenell et al, 2021). There is, to our knowledge, no study investigating the female rat behavioral response to USV emitted by female.…”
Section: Effect Of the Familiarity On The Rewarding Properties Of Usv And Consequences On Cocaine Intakementioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, while there is low intra-subject variability in terms of call types, acoustic parameters (i.e. duration, bandwidth, and mean peak frequency), and quantity of USV production in the same experimental context, there is a large inter-subject variability [31,32], depending on several factors, such as social status, sex, and strain [33]. This inter-subject variability in USV acoustic parameters and call profile, mirroring human prosody, suggests the existence of a vocal signature in rats allowing them to recognize individual conspecifics.…”
Section: Introductionmentioning
confidence: 99%